Institutionalization Specific of the Sverdlovsk Region Elite in the 1990-s (Publishing House Discourse-P, 2021)
The article is aimed at studying institutionalization specific of the Sverdlovsk Region elite. Methodology of the research is based on institutional, system and network approaches, which are used by the author to analyze the period of the 1990s - the essential stage in genesis and development of power groups in the region. In general, after the collapse of the USSR, institutionalization of regional elites was associated with elaboration of new stable forms of interaction between regional authorities, political institutions, as well as with foreign policy actors. Nomenclature origins, syncretism of power and property, and personalization of political leadership used to be the typical characteristics of the postSoviet regional elites. The article stresses that the key feature of Sverdlovsk Region elite institutionalization in the 1990s was the dominance of informal mechanisms of its functioning, which led to formation of power groups permeated with patron-client relationship. Despite the permanent conflicts between them, the unifying factor was motivation to legitimize their status, which determined their institutionalization features. The author also refers to them the conflict with the federal center and the project of the Ural Republic, the emphasis on regional identity, as well as the desire to gain international recognition. All these processes were related to political activities of the first Governor of the Sverdlovsk Region Eduard E. Rossel. It is concluded that the 1990s was the period of partial institutionalization of the regional elite in the Sverdlovsk Region, its main result was establishment of stable power groups. These groups have limited authority and no chance to create institutional rules of the game, but they can adapt to a new political situation, retain signs of regional identity and reproduce themselves as an elite even in conditions of political and economic instability.